Implementasi Software Quality Assurance pada Aplikasi E-Commerce Menggunakan Manual Testing dan Katalon Studio - Fahmi Ardiansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The reliability of an e-commerce application is essential to ensure smooth and secure user transactions. This study discusses the implementation of Software Quality Assurance (SQA) on a web-based e-commerce application to test the functionality of the developed system. The testing methodology used in this research combines manual testing and automated testing using the Katalon Studio tool, following the Software Testing Life Cycle (STLC) framework. Manual testing was focused on validating the user interface and user experience across core workflows, including user registration, authentication, cart management, and the checkout process. Meanwhile, Katalon Studio was utilized to execute automated test scenarios on these crucial features to accelerate regression testing and ensure system stability. The results indicate that from 42 test cases executed, the SQA approach successfully identified five functional defects across three modules, categorized by severity into two High-level defects (server error on registration and missing error handling on checkout), two Medium-level defects (client-side-only address validation and cart quantity logic), and one Low-level defect (insufficient logout notification display time). Four of the five defects were resolved, raising the test pass rate from 90.5% to 97.6% during regression testing. Automated testing demonstrated a significant time efficiency of approximately 95% compared to manual execution for regression scenarios. In conclusion, the combination of manual and automated testing proved capable of thoroughly verifying software quality, ensuring that the SQA Shop application functions according to the required specifications before its release to end-users.